Specific configuration of dendritic degeneration in pyramidal neurons of the medial prefrontal cortex induced by differing corticosteroid regimens - Cerqueira, João José (2007)
We previously demonstrated that hypercorticalism induces pronounced volumetric reductions in the rat medial prefrontal cortex (mPFC) and that these structural changes correlate with deficits in executive function. By applying 3-dimensional analysis of Golgi-Cox-stained material, we now demonstrate that corticosteroids can exert differential effects on dendritic arborizations of pyramidal neurons in lamina II/III of the mPFC. Treatment with the glucocorticoid receptor-selective agonist dexamethasone and with the natural adrenosteroid, corticosterone (CORT), results in significant reductions in the total length of apical dendrites in the pyramidal neurons in lamina II/III of the anterior cingulate/prelimbic and infralimbic cortices. Interestingly, although these treatments do not affect the number of dendritic branches, they are associated with impoverished arborizations in their distal portions and, in CORT-treated animals, with increased branching in the middle portions of the apical dendritic tree. Deprivation of corticosteroids by adrenalectomy leads to decreases in total apical dendritic length and spine number, but in this case, dendritic impoverishment was restricted to the middle/proximal segments of the dendritic trees. None of the treatments influenced the architecture of the basal dendrites. These results add to our knowledge of the morphological substrates through which corticosteroids may disrupt mPFC-dependent behaviors.